2018
DOI: 10.1007/s10533-018-0443-0
|View full text |Cite
|
Sign up to set email alerts
|

Geothermally warmed soils reveal persistent increases in the respiratory costs of soil microbes contributing to substantial C losses

Abstract: Increasing temperatures can accelerate soil organic matter decomposition and release large amounts of CO2 to the atmosphere, potentially inducing positive warming feedbacks. Alterations to the temperature sensitivity and physiological functioning of soil microorganisms may play a key role in these carbon (C) losses. Geothermally active areas in Iceland provide stable and continuous soil temperature gradients to test this hypothesis, encompassing the full range of warming scenarios projected by the Intergovernm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 72 publications
7
28
0
Order By: Relevance
“…Warmed soils differed from their ambient counterparts (Fig. 1b); total, dissolved organic, and microbial C, N, and P concentrations were lower in the warmed soils, mirroring previous studies that also report lower substrate concentrations and microbial biomass contents in the warmed soils at the same site [15][16][17][18] . Soil pH ranged from 4.4 to 6.0 and was slightly higher in the warmed soils (P < 0.05, n = 16, Pcorr > 0.1, Supplementary Table 1 and 2 for absolute values and significant differences, respectively).…”
Section: Warming Effects On Soil Physicochemical and Biological Propesupporting
confidence: 84%
See 1 more Smart Citation
“…Warmed soils differed from their ambient counterparts (Fig. 1b); total, dissolved organic, and microbial C, N, and P concentrations were lower in the warmed soils, mirroring previous studies that also report lower substrate concentrations and microbial biomass contents in the warmed soils at the same site [15][16][17][18] . Soil pH ranged from 4.4 to 6.0 and was slightly higher in the warmed soils (P < 0.05, n = 16, Pcorr > 0.1, Supplementary Table 1 and 2 for absolute values and significant differences, respectively).…”
Section: Warming Effects On Soil Physicochemical and Biological Propesupporting
confidence: 84%
“…The effects of long-term and short-to medium-term soil warming on abiotic and biotic properties and processes at these sites have been described in a range of publications. For example, Walker et al 16 , Marañón-Jiménez et al 17,18 , and Poeplau et al 19 identified considerable soil environmental changes in the warmed grassland plots, including reductions in topsoil C and nitrogen (N) pools by about 40% and decreased soil aggregation. These changes were accompanied by lower soil microbial biomass but higher soil respiration rates per unit of microbial biomass 16 , contradicting the concept of a physiological acclimation of microorganisms 16 .…”
Section: Introductionmentioning
confidence: 99%
“…acclimation" of CO2 effluxes at the higher soil temperatures, as suggested also in other laboratory studies in ForHot project by Marañón-Jiménez et al (2018) and Walker et al (2018).…”
Section: Discussionsupporting
confidence: 73%
“…First indirect support for this hypothesis comes from a study by Poeplau et al (2019) showing a strong warming-induced depletion of carbon concentration in the soils of these geothermal areas. However, soil microbial respiration rates were, contrary to the aforementioned hypothesis, reduced in these warmed soil as shown in recent laboratory incubation experiments (Marañón-Jiménez et al, 2018) most likely due to the reduced carbon contents in warmed soils and a subsequent decline in microbial biomass; however, mass-specific respiration rates increased with warming (Walker et al, 2018). Temperature effects 45 on soil respiration are thus highly complex and they need to be studied in the field to fully elucidate the interactions of plants, soil, and climatic variation.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation